Euthanasia between national legislation and international human rights law - Abdulaziz Alkitabi; Saif Nouri (الرافدین للحقوق, 2023)
The human aspires to perfection with his human instinct and always calls for a dignified and calm life without disease and pain, but there are stages in which the human finds himself either dependent or independent, where human life begins with a meager phase and then becomes strong. But temporary for sure because this strength does not last and then quickly returns to the first stage losing a large part of his independence the human fears this stage when he finds himself in the hospital unconscious or incapacitated and in a state of despair, afraid of needless surgeries and ineffective medicines, then he hopes to Find a solution to the problem that restricts him, to relieve pain. In this case, the term euthanasia comes as a last solution and treatment for a patient who does not expect recovery but …. The national laws and international agreements differed in their positions and were divided into supporters and opponents of this idea.